Digital Quantification of DNA Replication and Chromosome Segregation Enables Determination of Antimicrobial Susceptibility after only 15 Minutes of Antibiotic Exposure. (30th June 2016) - Schoepp, Nathan G.; Khorosheva, Eugenia M.; Schlappi, Travis S.; Curtis, Matthew S.; Humphries, Romney M.; Hindler, Janet A.; Ismagilov, Rustem F.
Abstract: Rapid antimicrobial susceptibility testing (AST) would decrease misuse and overuse of antibiotics. The "holy grail" of AST is a phenotype‐based test that can be performed within a doctor visit. Such a test requires the ability to determine a pathogen's susceptibility after only a short antibiotic exposure. Herein, digital PCR (dPCR) was employed to test whether measuring DNA replication of the target pathogen through digital single‐molecule counting would shorten the required time of antibiotic exposure. Partitioning bacterial chromosomal DNA into many small volumes during dPCR enabled AST results after short exposure times by 1) precise quantification and 2) a measurement of how antibiotics affect the states of macromolecular assembly of bacterial chromosomes. This digital AST (dAST) determined susceptibility of clinical isolates from urinary tract infections (UTIs) after 15 min of exposure for all four antibiotic classes relevant to UTIs. This work lays the foundation to develop a rapid, point‐of‐care AST and strengthen global antibiotic stewardship.